Synthesis, Characterization and Preliminary in vitro Antibacterial Screening Activity of Organotin(IV) Complexes Derivatives of 2-Amino-3-nitrobenzoic Acid - Choong, Chen-Shang; Ha, Sie-Tiong; Heng, Mei-Hsuan; Win, Yip-Foo (Asian Journal of Chemistry, 2014)
A total of four organotin(IV) carboxylate complexes have been synthesized and characterized quantitatively and qualitatively. Spectroscopy studies indicated that the coordination took place via oxygen atoms from the carboxylate anions. Moreover, all the complexes obtained as simple monomeric structure except complex 3 which was obtained as organodistannoxane dimer types. From the preliminary in vitro antibacterial screening activity, triphenyltin(IV) (complex 4) showed significant activity against Bacillus subtilis, Pseudomonas aeruginosa and Staphylococcus aureus and complex 2 only possessed better activity against Pseudomonas aeruginosa.